Doe Productivity Index of Saburai Goats at Sumberejo and Gisting Districts, Tanggamus Regency - Sulastri Sulastri; Siswanto Siswanto; Tri Yuliana Suhartanti; Kusuma Adhianto (Faculty of Animal Science, Universitas Gadjah Mada, 2018)
Saburai goat is a local genetic resource of Lampung Province. Sumberejo and Gisting district are Saburai goat development area. To increase the productivity of Saburai goats in both districts, selection on doe was done based on doe productivity index (DPI).The study was conducted from July 1st, 2017 to October 30th, 2017 to estimate the productivity of Saburai goats based on DPI. Materials of this research were a recording of mating, birth, and weaning weight of 50 of Saburai goat kids, kept in Sumberejo and Gisting district. The Does were in second parity and had weaned the goat kids. Variables observed were litter size (LS), kidding interval (KI), weaning weight (WW) and DPI. The Result indicated that in Sumberejo LS, KI, WW and DPI were 1.74±0.44 heads, 22.00±0.95 months, 21.48±4.04 kg, and 57.52±8.15 kg, respectively. While in Gisting LS, KI, WW, and DPI were 1.44±0.50 heads, 7.86±0.35 months, 15.18±4.32 kg, and 21.02±4.86 kg, respectively. It could be concluded that Saburai doe in Sumberejo district could be selected for breeding stock.